Encoding musical procedures by sequential transducers. Issue 3 (2nd September 2019) - Bozapalidou, Marianthi
Abstract : The aim of this paper is to establish the interconnection between musical functions and sequential transducers, thus enabling to transform musical properties into machine structural properties. Simply transitive left group actions deriving from generalized interval systems as well as musical metre partitioning and group preference rules G P R 2, G P R 3 are investigated in the proposed setup.